Using of Computer Technology for Enhancing Students Interest Learning in SMP Kristen Kefamenanu - Chrisinta, Debora; Ludji, Dian Grace; Bobu, Fetronela Rambu; Gelu, Leonard Peter; Benu, Luky Wandika; Pakaenoni, Lusilia Dos Santos; Simarmata, Justin Eduardo (Talenta Publisher, 2023)
SMP Kristen Kefamenanu has facilities and infrastructure such as the availability of classrooms, computer laboratory rooms, libraries and others. There are obstacles in the implementation of school learning that is still centered on teachers and does not use computer-aided learning media. Therefore, service activities are carried out to increase the interest and ability of students in the learning process through the use of computer technology. Some of the activities carried out to solve problems in SMP Kristen Kefamenanu: a) providing training on Mathematics learning media for SMP Kristen Kefamenanu and b) providing training on computer technology in the form of MS. Excel Software to SMP Kristen Kefamenanu. The results of the service activities carried out show that there is an increase for students in understanding mathematical concepts such as addition, subtraction, multiplication and division involving complex numbers. In addition, the existence of computer-aided media also increases students' interest for learning process.